FORMULATION AND EFFECTIVITY OF THE ANTIOXIDANT GEL PREPARATION CONTAINING ZEAXANTHIN AS ANTI AGING - SETIAWAN, FAJAR; NURDIANTI, LUSI; SRI, NENG (International Journal of Applied Pharmaceutics, 2021)
Objective: This study was conducted to determine the IC50 value of zeaxanthin, to know the formula that meets the requirements of the results of physical evaluation of gel preparations, and to know the effectiveness of zeaxanthin gel as an anti-aging on the skin. Methods: The preparation of this gel is made using zeaxanthin as an active substance with concentrations of 5%; 7.5%; and 10%. Tests conducted are organoleptic test, homogeneity test, pH, spreadability, viscosity, irritation test and cycling test. Tests conducted are organoleptic test, homogeneity test, pH, spreadability, viscosity, irritation test and cycling test. Tests on the effectiveness of zeaxanthin gel preparations against the backs of volunteers' hands were divided into 4 groups as well as testing conducted over 28 d. Results: The results showed a value of IC50 zeaxanthin of 9.044 μg/ml, all gel preparations met the requirements of physical evaluation results except in cycling test and test results of the effectiveness of zeaxanthin gel preparations on the backs of volunteer hands there was an increase in humidity with an average increase of 33.17%±11.867 and wrinkles obedience with an average decrease of 47.466%±7.115. Conclusion: Zeaxanthin can be formulated as gel anti-aging.